Biomarkers of disease activity and other factors as predictors of adalimumab pharmacokinetics in inflammatory bowel disease - Sánchez-Hernández, José Germán; Pérez-Blanco, Jonás Samuel; Rebollo, Noemí; Muñoz, Fernando; Prieto, Vanessa; Calvo, María Victoria (European journal of pharmaceutical sciences, 2020)
Inflammatory bowel disease (IBD) is commonly treated with adalimumab. The main objective of the study was to develop a population pharmacokinetic model of adalimumab in IBD patients evaluating the potential biomarkers of disease activity and other factors and its implications in adalimumab dosing. A prospective observational study was performed in adult patients diagnosed with Crohn's disease and ulcerative colitis treated with adalimumab and following a proactive therapeutic drug monitoring of serum concentrations. Adalimumab serum concentrations (ASC) were quantified mainly prior the administration using an enzyme-linked immunosorbent assay (ELISA). A population pharmacokinetic model was developed based on 303 ASC data of 104 IBD patients using non-linear mixed effect modelling approach. Sixty-five ASC from 20 additional patients were randomly selected as an external validation group. A one-compartment model with first order absorption and elimination best describe the ASC time course. Body mass index (BMI), faecal calprotectin (FCP), unexplained decline in ASC and the specific administration pen device exhibited significant influence on apparent clearance (p-value < 0.001). FCP was the inflammatory activity biomarker showing the most relevant impact on adalimumab exposure, higher than C-reactive protein and albumin, and may be useful for adalimumab dosing adjustment. The population-based pharmacokinetic model developed adequately characterized adalimumab exposure in IBD patients. The unexplained decline in ASC, FCP, BMI and the specific administration pen device were identified as meaningful variables significantly influencing adalimumab pharmacokinetics. [Display omitted]